PEMANFAATAN CLOUD COMPUTING UNTUK MENINGKATKAN EFISIENSI DAN SKALABILITAS SISTEM INFORMASI PERPUSTAKAAN DIGITAL - Febri Nahla; Zulaikha, Sri Rohyanti; Asnawi, Asnawi (Indonesian Journal of Library and Information Science, 2025)
This research illustrates the importance of implementing cloud computing in improving the operational efficiency and scalability of digital library information systems. Utilizing library research methods to review related literature, the research findings highlight that cloud computing enables libraries to respond faster to service needs, manage technology resources with flexibility, and improve user satisfaction through easier access and time savings. With a focus on resource management, automation, remote access, cost savings, data security, and analytics, this research shows that cloud computing not only provides an efficient solution, but is also an important strategic step in facing future challenges for digital libraries